Block-based physical modeling for digital sound synthesis of membranes and plates - Petrausch, Stefan; Rabenstein, Rudolf (International Computer Music Conference, ICMC 2005, 2005)
An application of block-based physical modeling for digital sound synthesis is presented in this paper. A membrane model in terms of a fourth order, two-dimensional partial differential equation is solved and discretized with the functional transformation method. The resulting algorithm constitutes an input-output description with input force and output velocity of the membrane. This input-output port is transformed to wave variables, such that the membrane model can be connected to an arbitrary wave digital filter network that includes nonlinear elements. The construction of these new interaction networks allows block-based physical modeling with mixed models. A real-time sound synthesis program is demonstrated, which simulates almost arbitrary two-dimensional resonators (e.g. membranes, wooden plates, metal plates) with almost arbitrary excitations (e.g. plucking, hammering). These sounds are produced only by changes of the physical parameters of the mode